2023
DOI: 10.3390/nu15030591
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Iron Metabolism and Ferroptosis as Novel Therapeutic Approaches in Cardiovascular Diseases

Abstract: Iron functions as an essential micronutrient and participates in normal physiological and biochemical processes in the cardiovascular system. Ferroptosis is a novel type of iron-dependent cell death driven by iron accumulation and lipid peroxidation, characterized by depletion of glutathione and suppression of glutathione peroxidase 4 (GPX4). Dysregulation of iron metabolism and ferroptosis have been implicated in the occurrence and development of cardiovascular diseases (CVDs), including hypertension, atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Metabolic plasticity confers a survival advantage to cancer cells for using nutrients, rapidly producing ATP, synthesizing biomass, and balancing reactive oxygen species [28]. Metabolic plasticity and ferroptosis are common metabolic pathways in tumor cells and are extensively studied in other diseases [29][30][31]. GO analysis showed that the abnormal expression of key genes in MPFDEGs primarily involves immune receptor activity and cytokine receptor binding, considering molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic plasticity confers a survival advantage to cancer cells for using nutrients, rapidly producing ATP, synthesizing biomass, and balancing reactive oxygen species [28]. Metabolic plasticity and ferroptosis are common metabolic pathways in tumor cells and are extensively studied in other diseases [29][30][31]. GO analysis showed that the abnormal expression of key genes in MPFDEGs primarily involves immune receptor activity and cytokine receptor binding, considering molecular functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, under the stimulation of chronic ischemia, the excessive deposition of collagen-rich extracellular matrix determines the pathological remodeling of the myocardium and causes an increase in mechanical strain in the border zone, which may lead to expansion of the fibrotic area, decreased tissue compliance and increased cardiac afterload (50)(51)(52)(53)(54). Existing research indicates that regulating FRGs can effectively reduce cardiac injury, fibrosis and pathological remodeling during ischemia (55). In the present study, the DEFRGs were found to be enriched in iron metabolism and the HIF-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of iron homeostasis results in iron overload, where excess ferrous iron (Fe 2+ ) induces lipid peroxidation via the Fenton reaction, leading to a redox imbalance [ 28 30 ]. A growing body of evidence underscores the pivotal role of ferroptosis in the pathogenesis of numerous cardiovascular diseases by disrupting normal cellular functions [ 31 33 ]. For instance, oxidized low-density lipoprotein (ox-LDL) has been implicated in the induction of endothelial dysfunction and ferroptosis through the modulation of ADM transcription and the activation of the AMPK signaling cascade [ 34 ].…”
Section: Discussionmentioning
confidence: 99%